ASSESSMENT OF KNOWLEDGE AND UTILIZATION OF MATERNAL AND CHILD HEALTH SERVICES AMONG WOMEN (International Journal of Food and Nutritional Sciences, 2022)
This paper attempts to study the knowledge and utilization of maternal and child health (MCH) services among woman residing in Badali and Gharuan village near Kharar. The total sample size was 60 women in selected rural areas Badali and Gharuan near Kharar (Punjab). Purposive sampling method was adopted to collect the data